2020
DOI: 10.3390/atmos12010034
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Tree Canopy and Chemical Reactions on the Dispersion of Reactive Pollutants in Street Canyons

Abstract: Traffic-related air pollution in street canyons can cause health problems for pedestrians. In order to clarify the behavior of reactive pollutants, such as NOx and O3, in street canyons, a computational fluid dynamics (CFD) model coupled with a chemistry model and tree canopy model was developed, and then, a set of numerical experiments were performed to investigate the impacts of chemical reactions and aerodynamic effects of trees planted in a canyon. The results were compared with the observation data. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The results obtained show that the presence of high vegetative barriers could result in negative impacts on pedestrians and cyclists; this could be because this type of vegetation offers temporary retention to particles from traffic, therefore increasing the time in which these particles are in the environment [18]. Similar results concluded that the effect of planting trees along the road to prevent emissions of reactive traffic pollutants from entering the sidewalk was low because trees also increase pollutant concentrations by weakening the wind [27]. The position where vegetation is planted has also been found to be more critical than the area and volume of vegetation for reduction in particulate matter concentration [4].…”
Section: Assessment Of Pedestrian Exposurementioning
confidence: 65%
“…The results obtained show that the presence of high vegetative barriers could result in negative impacts on pedestrians and cyclists; this could be because this type of vegetation offers temporary retention to particles from traffic, therefore increasing the time in which these particles are in the environment [18]. Similar results concluded that the effect of planting trees along the road to prevent emissions of reactive traffic pollutants from entering the sidewalk was low because trees also increase pollutant concentrations by weakening the wind [27]. The position where vegetation is planted has also been found to be more critical than the area and volume of vegetation for reduction in particulate matter concentration [4].…”
Section: Assessment Of Pedestrian Exposurementioning
confidence: 65%